Let's explore diabetes with owls [compact disc, unabridged] - Sedaris, David (Hachette Audio, 2013)
"From the unique perspective of David Sedaris comes a new book of essays taking his readers on a bizarre and stimulating world tour. From the perils of French dentistry to the eating habits of the Australian kookaburra, from the squat-style toilets of Beijing to the particular wilderness of a North Carolina Costco, we learn about the absurdity and delight of a curious traveler's experiences. Whether railing against the habits of litterers in the English countryside or marveling over a disembodied human arm in a taxidermist's shop, Sedaris takes us on side-splitting adventures that are not to be forgotten" -- from publisher's web site.